Chapter VIII: El maestro de carrasqueda como explicación de San Manuel Bueno, mártir. - Díaz-Peterson, Rosendo (Las Novelas de Unamuno, 1988)
Presents the book "Las Novelas de Unamuno," written by Díaz-Peterson, with a prologue by Antonio Carreño and published by Scripta Humanistica. It discusses the philosophy and literary works of Spanish writer Miguel de Unamuno including his novels "Paz en la Guerra," "Abel Sánchez" and "San Manuel Bueno, mártir."